2014
DOI: 10.1063/1.4868203
|View full text |Cite
|
Sign up to set email alerts
|

Nearly constant magnetic entropy change and adiabatic temperature change in PrGa compound

Abstract: Effect of magnetic polarons on the magnetic, magnetocaloric, and magnetoresistance properties of the intermetallic compound HoNiAl Large magnetic entropy change in the metallic antiperovskite Mn 3 GaCThe magnetic properties and magnetocaloric effect (MCE) of PrGa compound are studied in detail. Both thermomagnetization curves and heat capacity curves indicate that PrGa compound undergoes a transition from ferromagnetic (FM) to antiferromagnetic (AFM) phase at T t $ 27 K and a transition from AFM to paramagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…We also studied the thermal expansion, MCE and MR of PrGa compounds in details 8 . Our previous studies showed that a nearly constant value of ΔS M was observed when the field changes from 0 to 5 T 19 . A nearly constant ΔS M has also been observed in LaFe 11.44 Al 1.56 compound 20 , while the cause of plateau on the MCE curve in PrGa compound is different from that in LaFe 11.44 Al 1.56 compound.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…We also studied the thermal expansion, MCE and MR of PrGa compounds in details 8 . Our previous studies showed that a nearly constant value of ΔS M was observed when the field changes from 0 to 5 T 19 . A nearly constant ΔS M has also been observed in LaFe 11.44 Al 1.56 compound 20 , while the cause of plateau on the MCE curve in PrGa compound is different from that in LaFe 11.44 Al 1.56 compound.…”
mentioning
confidence: 93%
“…However, no SR transition is observed in PrGa according to the previous Mössbauer spectroscopy experiment 18 . The magnetic property, MR and MCE of PrGa compound have been reported 8 19 , but the magnetic structure and physical mechanism of MR and MCE are still not clear.…”
mentioning
confidence: 99%
“…33 In addition, interesting magnetic properties, transport properties and MCEs were also found in TmGa and PrGa compounds. [34][35][36][37] In this paper, we investigate the magnetic properties and MCEs of NdGa compound. The correlations between MCE and magnetic transitions will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The RGa (R¼ rare earth) compounds have been known since the 1960s [1][2][3][4] and are enjoying a revival of interest due to their possible use in low-temperature magnetocaloric refrigeration applications [5][6][7][8][9][10][11][12]. They crystallise in the orthorhombic CrB-type Cmcm structure with both the R and Ga atoms occupying 4c sites with the m2m point symmetry.…”
Section: Introductionmentioning
confidence: 99%